2016
DOI: 10.1016/j.actbio.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stromal cell sheet therapy for bisphosphonate-related osteonecrosis of the jaw in a rat model

Abstract: Bisphosphonates are frequently used to treat osteoporosis, bone metastasis of various cancers, and other diseases. However, bisphosphonate related-osteonecrosis of the jaw (BRONJ) is an intractable disease because it often recurs after surgery or is exacerbated following conservative treatment. Therefore, an alternative approach for treating BRONJ is needed. In this study, we developed a bone marrow-derived multipotent mesenchymal stromal cell (MSC) sheet to treat BRONJ and investigated the effect of MSC sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 58 publications
(79 reference statements)
4
62
2
3
Order By: Relevance
“…Since the therapeutic effect of cell therapy is thought to be derived from factors secreted from transplanted cells , it is generally believed that prolonged presence of donor cells in the target organs leads to improved efficacy. Indeed, the long‐term survival of the cell sheets on the target organ resulted in stronger therapeutic effects as compared with injection of cells in various disease models . Furthermore, we previously showed that transplantation of an HGF‐tg MC‐sheet onto the kidney surface suppressed kidney injury to a significantly greater degree than remote transplantation (on femoral vascular bed) of the HGF‐tg MC‐sheets .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the therapeutic effect of cell therapy is thought to be derived from factors secreted from transplanted cells , it is generally believed that prolonged presence of donor cells in the target organs leads to improved efficacy. Indeed, the long‐term survival of the cell sheets on the target organ resulted in stronger therapeutic effects as compared with injection of cells in various disease models . Furthermore, we previously showed that transplantation of an HGF‐tg MC‐sheet onto the kidney surface suppressed kidney injury to a significantly greater degree than remote transplantation (on femoral vascular bed) of the HGF‐tg MC‐sheets .…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow cells were isolated from male Sprague‐Dawley (SD) rats for in vitro experiments, as well as from SD Tg (CAG‐enhanced green fluorescent protein [EGFP]) rats and Luc Tg Lewis rats , for in vivo experiments, as previously described . Briefly, after cutting the epiphyses of femora and tibiae, the bone marrow cavity was flushed with complete medium (a‐MEM; Minimum Essential Medium; Life Technologies, Carlsbad, CA, USA supplemented with 1% penicillin–streptomycin [Life Technologies, Rockville, MD, USA] and 10% fetal bovine serum [Japan BioSerum]), using a 23‐gauge needle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell‐based regenerative medicine, involving the transplantation of cells into patients, is a promising therapeutic strategy. Various cell transplantation methods have been investigated, including the injection of cell suspensions, the transplantation of fabricated tissues with biodegradable scaffolds, and the transplantation of cell sheets . Cell sheet transplantation has advantages compared with these other methods.…”
Section: Introductionmentioning
confidence: 99%